INFLUENCE OF SUBDUCTION ZONE SETTINGS ON THE ORIGIN OF FOREARC FLUIDS: HALOGEN CONCENTRATIONS AND 129I/I RATIOS IN WATERS FROM KYUSHU, JAPAN - Tomaru H.; Lu Z.; Fehn U.; Ohsawa S.; Amita K. (My University, 2007)
Fluid migration in subduction zones is one of the key phenomena to understand the global mass transfer system. While active volcanoes provide the most recognizable conduits for fluid flow in active margins, the existence of a large number of active fluid seepages demonstrates that other forms of fluid release are also important in subduction zone settings. The authors collected fluid samples from springs and wells across the forearc area in Kyushu, a southwestern island of Japan, covering hot spring activities associated with active volcanism and the Median Tectonic Line (MTL), a major fault system present in the southwestern part of Japan. In order to determine sources of these fluids, halogen concentrations as well as 129I/I and 36Cl/Cl ratios were measured in samples from several locations. While Cl concentrations of the forearc fluids in Kyushu range between seawater and meteoric water value, I concentrations are considerably higher than seawater value. Fluids in the Miyazaki area are much higher in I, and somewhat higher in Br, than waters in the Oita area, which is closely associated with the MTL. The differences between those two areas are also pronounced in 129I/I ratios, which range between 800 and 900 × 10-15 in the Oita area and between 100 and 360 × 10-15 in the Miyazaki area. The 129I/I ratios obtained from the Oita area are compatible with an I derivation from subducting marine sediments, similar to findings from an earlier investigation of fluids collected from Satsuma-Iwojima, an active volcano south of Kyushu Island. In the Miyazaki area, on the other hand, I ages are too old to be derived from currently subducting marine sediments and point to a derivation from old organic-rich materials in the upper plate of the forearc region. The results demonstrate the presence of very different fluid systems in the forearc area of Kyushu: old CH4-rich fluids dominate in the seaward side of the forearc, while fluids close to the MTL and the Quaternary Volcanic Front demonstrate derivations from subducting marine sediments. The latter fluids in the MTL area probably are transported through the fractures associated with the fault activities, suggesting that this fault system reaches the transition zone between upper and lower plates in this region. © 2006 Elsevier Ltd. All rights reserved.
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная